Beacon technology for real-time informing the traffic network users about the environment - Periša, Marko; Cvitić, Ivan; Peraković, Dragan; Husnjak, Siniša (Transport, 2019)
Informing the users about their environment is of extreme importance for their full and independent functioning in the traffic system. Today’s development of technology provides the user the access to information about their environment by using the smartphone device at any moment if there is a defined applicative solution. For this, it is necessary to define the user’s environment according to the Ambient Assisted Living (AAL) concept, which understands adequate technology of gathering, processing and distribution of information. This paper presents the proposal of the solution for informing the traffic network users about the environment for the defined group of users based on the beacon technology. The mentioned solution is based on the results of two separate studies about the needs of users who move along a part of the traffic network. The aim of the proposed solution is to provide the user with precise and real-time information and to raise the level of safety during movement.